(untitled) (International Current Pharmaceutical Journal, 2014)
Acetaminophen (APAP) is a common antipyretic drug and leads to liver failure at over dose. In this study, the hepatoprotective effect of Aqueous Methanolic Bark Extract of Oroxylum indicum (L.)Vent. (AMBEOI) has been evaluated in rat model. Rats were treated with 1000 mgkg?1 body weight of APAP alone or with AMBEOI (10, 50 and 100 mgkg?1). Serum Alanine aminotransferase (ALT), Aspartate aminotransferase (AST), Lipid peroxidation (LPO) in liver tissues were estimated 24 hrs after APAP and AMBEOI treatment. AMBEOI administration effectively reduced serum level of ALT and AST released from liver cells when compared to APAP treated group. AMBEOI also inhibited production of LPO in the liver tissues of APAP treated rats. Histopathological examination of liver samples revealed reduced necrotic areas in AMBEOI treated APAP group compared to APAP alone treated group. Together, this study confirmed the hepatoprotective activities of AMBEOI in APAP induced liver damage in rat. DOI: http://dx.doi.org/10.3329/icpj.v3i2.17511 International Current Pharmaceutical Journal, January 2014, 3(2): 223-227